Sistematização da assistência de enfermagem (SAE) em um hospital pediátrico de ensino: uma pesquisa-ação - Souza, Marilia Fernandes Gonzaga de (2010)
The incessant search if nurse for qualify nursing care makes the Nursing Assistance Systematization, a current topic of discussion throughout the country, not only in order to comply the legal requirements of their practice, but especially by the expected benefits of its application. In this meaning, this research had a qualitative approach, developed for a way of research-action. The general purpose was to analyze the change in the nursing practices in a pediatric teaching hospital, based on construction and implementation of Nursing Assistance Systematization by the nursing team. The results had the thematic analysis of Paulo Freire and were shown in the form of reports. To achieve these purposes, it began by steps pre-trial, to review the charts of the institution and an approach with the managers. In the situational diagnosis of nursing practices without the systematization followed by applying a questionnaire with a nursing team and a focal group with nurses. These ways supported the implementation stage of the Nursing Assistance Systematization which developed actions associate such as focal group with the nurses about the nursing history, capacity with the nursing team about the Nursing Assistance Systematization, development, application and reworking of printed, and discussions in the small groups. The evaluations of the changes after the actions of the research occurred through individual interview with the nurses, to check the results. The charts review confirmed the deficit in the records performed by the nurse on the chart, which reinforced the need for implementation of Nursing Assistance Systematization, an argument used on the meeting with the managers, who promptly agree with the search. The questionnaire and the focal group with the nurses reveal a process of nursing work without systematization, showing gaps in practices, but also obtained relate of expectations of improvements in quality of care as of Nursing Assistance Systematization, furnishing data to the development of ways following-up. The prints were gradually used and modified as the team understood the Nursing Assistance Systematization and its purposes through capacity course. The final evaluation pointed to the partial implementation of the stages of Nursing Assistance Systematization had been institutionalized at the history and the development of nursing, beyond difficulties with diagnosis and prescription of nursing, in later representing a paradigm shift. This search collaborated to change the view about the Nursing Assistance Systematization by nursing team at the institution had been revealed through introduction of new practices in the process of nursing work, as examination of physical exam of the patient, the interview in the admission of customers on service and the daily monitoring by nursing through development of nursing. Before addition, it was noted which the purposes of this search were achieved, since were analyzed the changes in the nursing practices with the systematization. The research-action achieved proposes of the involvement of nursing team in changing their practices. This search contributed to the implementation of the Nursing Assistance Systematization in a pediatric teaching hospital and showed which is possible to seek resolution of problems when the objective is of the group and gave access for further searches within this theme